2014
DOI: 10.1039/c4ta02695k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet soaking on surface electronic structures of solution processed ZnO nanoparticle films in polymer solar cells

Abstract: Abstract:We systematically show the effect of UV-light soaking on surface electronic structure and chemical states of solution processed ZnO nanoparticle (ZnONP) films in UHV, dry air and UV-ozone. UV exposure in UHV induces a slight decrease in work function and surfacedesorption of chemisorbed oxygen, whereas UV exposure in presence of oxygen cause an increase in work function due to oxygen atom vacancy filling in the ZnO matrix. We demonstrate that UV-light soaking in combination with vacuum or oxygen can t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 51 publications
(70 reference statements)
7
47
0
Order By: Relevance
“…[26][27][28] In the event that such UV-treated ZnO layers are placed again in ambient air the reverse process occurs within minutes. We completed a cell with such UVN treated ZnO layer but placed in air, and observed a performance no different than the reference cell.…”
Section: Influence Of Uvn Treatment On Device Performancementioning
confidence: 99%
“…[26][27][28] In the event that such UV-treated ZnO layers are placed again in ambient air the reverse process occurs within minutes. We completed a cell with such UVN treated ZnO layer but placed in air, and observed a performance no different than the reference cell.…”
Section: Influence Of Uvn Treatment On Device Performancementioning
confidence: 99%
“…In this regard, many studies have focused on engineering the surface of ZnO films through improving the interfacial electrical properties, better aligning energy-level and controlling the surface energy. Among the most efficient methods to modify the ZnO surface are the ultraviolet (UV) or UV-ozone treatment, [32][33][34][35][36][37] and the incorporation of a surface modification interlayer, such as a coordination polymer 38,39 or a self-assembled monolayer (SAM). [40][41][42][43][44] However, UV treatment may cause severe degradation of the device lifetime whereas the insulating properties of coordination polymers results in a trade-off between effective passivation and charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PA molecules, as used in this study undergo tridentate binding to the ZnO surface, meaning that each PA molecule occupies three surface sites. The fact that the presence of the SAM does not reduce the strength of the light‐induced WF shift suggests that this phenomenon is not entirely caused by changes of the ZnO surface chemistry, but may also involve internal surfaces such as grain boundaries . As for the bare ZnO, the WF increases again when these UV‐soaked ZnO samples are stored in the dark (triangles in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Self‐assembled monolayers (SAMs) based on phosphonic acids (PAs) are frequently employed as interface modifiers to tune the WF of ZnO, enabling efficient injection of electrons and even holes into a wide range of semiconducting molecules and polymers . In contrast, ultraviolet (UV) illumination (light‐soaking) was shown to lead to transient and persistent changes of the WF of metal oxides, and particularly of ZnO . Several studies deal with the influence of the sample environment during UV light soaking on the strength and direction of the WF shift .…”
Section: Introductionmentioning
confidence: 99%